Tissue-based genomic profiling of 300,000 tumors highlights the detection of variants with low allele fraction - Saumya D. Sisoudiya; Hanna Tukachinsky; Rachel B. Keller-Evans; Alexa B. Schrock; Richard S. P. Huang; Ole Gjoerup; Michael J. Pishvaian; Rachna Shroff; Ethan S. Sokol; Lucas Dennis; Garrett M. Frampton; Smruthy Sivakumar (npj Precision Oncology)
Abstract Tumor tissues obtained in the clinical setting typically have low purity and display treatment-associated genetic heterogeneity, contributing to variants at low variant allele fractions (VAF). We present a pan-cancer landscape and the therapeutic impact of somatic variants detected at low VAF (≤10%) from tumor tissues in 331,503 patients, across 78 tumor types, that received an FDA-approved comprehensive genomic profiling (CGP) test targeting ~324 genes during routine clinical care. 29% of patients had at least one variant detected at VAF ≤10% and 16% at VAF ≤5%. Among the frequently diagnosed tumors, several cases showed low VAF variants: pancreatic (37%), non-small cell lung cancer (35%), colorectal (29%) and prostate (24%). Treatment resistance-associated alterations had lower median VAF than driver alterations, although variants with VAF ≤5% comprised both driver and resistance alterations. This highlights the importance of CGP in detecting low VAF variants, to better inform clinical actionability and guide personalized treatment for patients with cancer.